Relationship between circulating VCAM-1, ICAM-1, E-selectin and MMP9 and the extent of coronary lesions - Santos, Jéssica Cavalcante dos; Cruz, Marina Sampaio; Bortolin, Raul Hernandes; Oliveira, Katiene Macêdo de; Araújo, Jéssica Nayara Góes de; Duarte, Victor Hugo Rezende; Silva, Ananília Medeiros Gomes da; Santos, Isabelle Cristina Clemente dos; Dantas, Juliana Marinho de Oliveira; Paiva, Maria Sanali Moura de Oliveira; Rezende, Adriana Augusto; Hirata, Mario Hiroyuki; et al. (Clinics (São Paulo, Brazil), 2018)
Inflammatory molecules play a role in the development of atherosclerosis, which is the primary origin of cardiovascular disorders. However, to the best of our knowledge, no study has attempted to investigate the relationship between these circulating molecules and the prediction of cardiovascular risk. The present study aimed to investigate the relationships of vascular cell adhesion molecule-1, intercellular adhesion molecule-1, E-selectin and matrix metalloproteinase 9 serum concentrations with the extent of coronary lesions. Seventy-four individuals who were undergoing coronary angiography for the first time for diagnostic purposes were enrolled in this study. The extent of the coronary lesion was assessed using the Friesinger Index, and subjects were classified into four groups: no lesions, minor lesions, intermediate lesions and major lesions. Serum biochemical parameters and serum concentrations of vascular cell adhesion molecule-1, intercellular adhesion molecule-1, E-selectin and matrix metalloproteinase 9 were analyzed. The vascular cell adhesion molecule-1 concentration was higher than 876 ng/mL in individuals with intermediate and major lesions (p<0.001 and p=0.020, respectively). Moreover, logistic regression analysis showed that these patients had an increased risk of having an intermediate lesion (p=0.007). Interestingly, all individuals with major lesions had vascular cell adhesion molecule-1 concentrations higher than 876 ng/mL. No association was found between the concentrations of the other proteins and the Friesinger Index. Serum vascular cell adhesion molecule-1 may be associated with the extent of coronary lesions. Moreover, it may represent an alternative to improve the cardiovascular risk classification in patients without acute coronary syndrome.